Trends and challenges in content curation 2014-2024 - Guallar, Javier (Anuario ThinkEPI, 2024)
The evolution of content curation from 2014 to 2024 is analyzed, identifying trends such as the increase in curated content in the media and information products based on curation (newsletters, live news, or multimedia reports). A change in the practice of curation on social networks is observed, from specialized platforms to mass social networks. Finally, future challenges for curation are proposed, including the need to advocate for links on social networks, increase external and personalized curation in the media, address misinformation, and integrate artificial intelligence without replacing human work.